Mapping a winning strategy : developing and executing a successful strategy in turbulent markets - Baaij, Marc; Reinmoeller, Patrick (Emerald Publishing Limited, 2018)
Mapping a WinningStrategyintroduces a new mapping method for creating and executing aneffective business strategy. By mapping out the most effective strategy, organizationscan make winning operational choices in today's VUCA (volatile, uncertain, complex and ambiguous) business environment.